Unconventional monetary policy and international equity capital flows to emerging markets - Andreou, Christoforos K.; Dimic, Nebojsa; Piljak, Vanja; Savvides, Andreas (Wiley, 2021)
This paper examines the relationship between monetary policies pursued by three major central banks (U.S. Federal Reserve, European Central Bank and Bank of Japan) and net equity capital flows to emerging markets (EMs) by global investment funds. We focus on two aspects of central bank policy: The growth of central bank assets and the surprise element of asset growth. We find, first, positive, economically large and statistically significant spillovers from the U.S. Federal Reserve asset growth to EM equity inflows following the adoption of unconventional monetary policies. Second, U.S. Federal Reserve and (to a lesser extent) European Central Bank asset growth surprises are negatively related to EM capital flows.
Keywords: emerging markets; international capital flows; unconventional monetary policy; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|